DANCE AND TRAINING WITH WEIGHT IN THE STATE OF ANIMAL IN ELDERLY (Fiep Bulletin - online, 2019)
The various types of physical activity may trigger different emotional states in the practitioners. Therefore, theobjective of the present research was to investigate the influence of the free dance and weight training (WT) upon the state ofmind (SM) of elderly women of the active life project. This study is a field research with a quantitative and direct approach and adescriptive procedure method, carried out in the municipality of Patos, in the State of Paraíba, in 2017, the target public wereelderly women of the active life project developed by the Bachelor in Physical Education Course, of the Integrated Faculties ofPatos. An instrument with 14 adjectives was used, organized in the form of a scale, the LEA-Ri – List of States of Mind, reducedand Illustrated. The states of mind of 09 participants of the dance group and weight training were assessed by means of aquestionnaire, before and after a session of each activity. All the participants carried out both activities, which had the duration ofone hour each, on separate days. The fixed variable among the modalities was the music selection. The data obtained wassubmitted to comparative analysis by means of graphs. It is thereby perceived, that the practice of dance and weight traininginfluenced the state of mind of the elderly women of the active life project. The results demonstrated a positive improvement of theadjectives when initiating and ending the lessons, there was an increase of motivation to exercise and socialize, causing theindividuals to feel more comfortable and happier.